Is WX CEN a possible type Ia supernova progenitor with wind-driven mass transfer? - Qian, S.-B. (2013)
WX Cen is one of a few compact binary supersoft X-ray sources (CBSS) in the Galaxy that is a possible Type Ia supernova (SN Ia) progenitor. The supersoft X-ray radiation is explained as hydrostatic nuclear burning on the surface of the white dwarf component that is accreting hydrogen from a stellar companion at a high rate. If the mass donor in this system has a low mass, as has been suggested in the literature, one would expect a high wind-driven mass transfer rate. In that case, the orbital period of the system should increase. To test this theoretical prediction, we have monitored the system photometrically since 2010. By using four newly determined eclipse timings together with those collected from the literature, we discovered that the orbital period is decreasing at a rate of dP/dt = -5.15 × 10-7 days yr -1. The long-term decrease in the orbital period is contrary to the prediction that the system is powered by wind-driven accretion. It therefore seems plausible that the mass donor could be more massive than the white dwarf, and that the mass transfer is driven by the thermal instability of the donor star. This finding suggests that WX Cen is a key object to check the physical mechanisms of mass accretion in CBSS. The corresponding timescale of the period change is about yr, indicating that WX Cen may evolve into an SNe Ia within one million years in the Galaxy.